Investigating radiation responsiveness in rectal cancer - Hassall, James (2021)
Currently rectal cancer patients undergoing radiotherapy are subject to a ‘watch-and-wait’ scenario whereby the clinician and patient are not certain if the tumour is responding to the radiotherapy until completion. Real-time monitoring of response to radiotherapy may be possible via liquid biopsy testing and it is hoped that this will inevitably improve outcome by streamlined patient stratification. Liquid biopsies are a promising method to interrogate the molecular characteristics of the tumour and determine presence of the tumour in real-time by blood test. This is possible when dying cells release DNA into the blood stream (cell-free DNA). This also occurs in tumour cells (circulating tumour DNA) at a higher rate due to their instability, producing regular injections of DNA into the blood stream. Each tumour contains a plethora of mutations which can be identified in cell free DNA by an appropriate mutation detection methodology. Cell-free DNA is highly fragmented (130-170bp), low in mutant allele frequency (as low as 0.01%) and low in concentration (1-100ng/ml of blood). Therefore, these characteristics present a major hurdle for mutation detection methods to determine presence of circulating tumour DNA.